Mechanical Power in Prone Position Intubated Patients with COVID-19-Related ARDS: A Cohort Study - Roberto Stalla Alves da Fonseca; Viviane Martins Correa Boniatti; Michelle Carneiro Teixeira; Alessandra Preisig Werlang; Francielle Martins; Pedro Henrique Rigotti Soares; Leonardo da Silva Marques; Wagner Luis Nedel (Critical Care Research and Practice)
Background. Respiratory monitoring of mechanical ventilation (MV) is relevant and challenging in COVID-19. Mechanical power (MP) is a novel and promising monitoring tool in acute distress respiratory syndrome (ARDS), representing the amount of energy transferred from the ventilator to the patient. It encompasses several setting parameters and patient-dependent variables that could cause lung injury. MP can therefore be an additional tool in the assessment of these patients. Objective. This study aims to evaluate respiratory monitoring through MP and its relationship with mortality in patients with COVID-19-related ARDS (CARDS) under mechanical ventilation (MV) and prone position (PP) strategies. Methods. Retrospective, unicentric, and cohort studies. We included patients with CARDS under invasive MV and PP strategies. Information regarding MP, ventilation, and gas exchange was collected at 3 moments: (1) prior to the first PP, (2) during the first PP, and (3) during the last PP. We tested the relationship between MP and VR with in-hospital mortality. Results. We included 91 patients. There was a statistically significant difference in MP measurements between survivors and nonsurvivors only in the last prone position (p<0.001). This is due to the significant increase in MP measurements in nonsurvivors (difference from the baseline: 3.63 J/min; 95% CI: 0.31 to 6.94), which was not observed in the group that survived (difference from the baseline: 0.02 J/min; 95% CI: −2.66 to 2.70). In multivariate analysis, MP (p=0.009) was associated with hospital death when corrected for confounder variables (SAPS 3 score, mechanical ventilation time, age, and number of prone sessions). Conclusions. MP is an independent predictor of mortality in PP patients with CARDS.